2023
DOI: 10.1111/anae.16072
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of prehabilitation in patients undergoing elective cardiac surgery

Abstract: Summary The feasibility, safety and efficacy of prehabilitation in adult patients awaiting elective cardiac surgery are unknown. A total of 180 participants undergoing elective cardiac surgery were allocated randomly to receive either standard pre‐operative care or prehabilitation, consisting of pre‐operative exercise and inspiratory muscle training. The primary outcome was change in six‐minute walk test distance from baseline to pre‐operative assessment. Secondary outcomes included change in inspiratory muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Both results are in line with the results found in the current literature [ 56 59 ]. A recently published randomized control trial showed that a prehabilitation program before elective cardiac surgery improved 6MWD significantly in the subgroup of sarcopenic patients [ 60 ]. These results indicate that cardiac prehabilitation programs should include exercises to increase endurance and mobility to prepare especially older patients with sarcopenia for the procedure and the convalescent phase of relative inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Both results are in line with the results found in the current literature [ 56 59 ]. A recently published randomized control trial showed that a prehabilitation program before elective cardiac surgery improved 6MWD significantly in the subgroup of sarcopenic patients [ 60 ]. These results indicate that cardiac prehabilitation programs should include exercises to increase endurance and mobility to prepare especially older patients with sarcopenia for the procedure and the convalescent phase of relative inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Akowuah et al. is, therefore, an important addition to the published literature [3]. The authors conducted a randomised controlled trial in 180 patients undergoing cardiac surgery, assessing feasibility, safety and efficacy of exercise and inspiratory muscle training prehabilitation interventions.…”
mentioning
confidence: 99%
“…In With regard to prehabilitation research in cardiac surgery, there is an accompanying qualitative study by Harrison et al [4]. The authors have concentrated on the experiences of patients and staff enrolled in the cardiac prehabilitation trial conducted by Akowuah et al [3]. Whilst this is a small study, with 16 male patients and eight staff members included, it is important as it explores the fears cardiac patients and staff have about exercise in this highrisk group, which may directly impact on the feasibility and efficiency of the intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation